Análise de desempenho de rota no perímetro urbano de Manaus: estudo de caso da operação de veículos de carga na av. General Rodrigo Otávio - Freitas, Bruna dos Santos (Brasil, 2022)
Urban mobility is a major challenge for cities. The lack of transport planning and infrastructure in this area linked to the increase in vehicle circulation has as consequences several disorders such as: congestion, lack of fluidity, traffic accidents, among others. In this context, studies related to Traffic Engineering are very important. The present work has as its object of study the section of Avenida General Rodrigo Otávio that begins at the Complexo Viário Gilberto Mestrinho (CVGM) and ends at its confluence with the Suframa Roundabout. This study seeks to analyze the route performance of freight vehicles based on the speed and delay methodology according to the Technical Bulletin of the Traffic Engineering Company. From the data collected in the field, the travel speeds that are developed by the cargo vehicles, the stop times and reasons for delays were verified. The results showed the critical segments. Being, in the CVGM-Distrito direction, the critical section between the traffic light in front of Baratão da Carne and the traffic light at the intersection with Rua Rubens Benzecry; and towards Distrito-CVGM, the section between the traffic light in front of the Shell Post and the traffic light in front of Força Construtiva. In addition, knowledge of such factors serves as a basis to support transport planning, so that interventions can be made on the spot.